KOLABORASI MULTISTAKEHOLDER DALAM PERCEPATAN PENURUNAN STUNTING DI KABUPATEN KOLAKA - Maulid; Taslim Fait; Abdul Sabaruddin; La Ode Muhammad Elwan (Journal Publicuho, 2025)
This study aims to analyse the Kolaka District Government's policies for accelerating stunting reduction, examine the implementation of multi-stakeholder collaboration, and identify factors that support or hinder the effectiveness of this collaboration. The research employs a descriptive qualitative approach, utilising data collection techniques such as in-depth interviews, documentation studies, and participatory observation. The results indicate that the Kolaka Regency government has demonstrated commitment through regional regulations and the establishment of a cross-sectoral institutional structure via the Stunting Reduction Acceleration Team (TPPS). The team has effectively consolidated the roles of government, the private sector, civil society, and educational institutions. Key supporting factors include the commitment of local leaders, the integration of target data based on names and addresses, and the strengthening of communication forums. Inhibiting factors consist of the limited capacity of stakeholders, disproportionate budget allocations, and weak integrated monitoring and evaluation systems. This research highlights the significance of adaptive and inclusive collaborative governance in enhancing the effectiveness of stunting reduction policies in the regions.